Monetary union and fiscal federalism - Kenneth M. Kletzer; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
Does a monetary union need fiscal shock absorbers helping the participating countries to cope with asymmetric shocks? The consensus in the debate over EMU argues that the answer is yes. In this paper, we revisit the issue, building on a dynamic, general equilibrium framework of regions in a monetary union exposed to asymmetric shocks. We show that inter-regional taxes and transfers can stabilize regional employment or consumption, but not both. The welfare effects of such stabilization are, however, ambiguous. In contrast to a popular argument in the EMU debate, inter-regional taxes and transfers do not reduce the incentives for goods and labor market deregulation in the regions, provided that the degree of trade integration among the regions is large. There is, however, reason to coordinate regional reform policies to avoid adverse effects on the aggregate performance of the union.
Keywords: 330; Währungsunion; Finanzföderalismus; Schock; Regionale Entwicklung; Allgemeines Gleichgewicht; Finanzausgl